Carboplatin and Paclitaxel versus Cisplatin, Paclitaxel and Doxorubicin for first-line chemotherapy of Advanced Ovarian Cancer: A Hellenic Cooperative Oncology Group (HeCOG) study - Aravantinos, G.; Fountzilas, G.; Bamias, A.; Grimani, I.; Rizos, S.; Kalofonos, H.P.; Skarlos, D.V.; Economopoulos, T.; Kosmidis, P.A.; Stathopoulos, G. P.; Briasoulis, E.; Pectasides, D.; et al. (European Journal of Cancer, 2008)
Introduction: The combination of Carboplatin and Paclitaxel is considered the standard of care as initial chemotherapy for Advanced Ovarian Cancer (AOC). We compared this regimen with the combination of Cisplatin, Paclitaxel and Doxorubicin. Patients and methods: Patients with AOC were randomised to either six courses of Paclitaxel 175 mg/m2 plus Carboplatin 7AUC or Paclitaxel at the same dose plus Cisplatin 75 mg/m2 plus Doxorubicin 40 mg/m2. Results: Analysis was performed on 451 patients. The treatment groups were well balanced with regard to patient and disease characteristics. Performance status (PS) was better in the anthracycline arm. In terms of severe toxicity, the only significant difference between the two groups was the development of febrile neutropaenia in the anthracycline arm. Overall response rate was similar in both groups. With a median follow-up of 57.5 months, a marginal significance towards improved Progression-Free Survival (PFS) was noted in favour of the anthracycline arm, whilst there was no difference in overall survival. In multivariate analysis the hazard of disease progression at any time was significantly decreased by 25.5% for patients of the anthracycline arm. Conclusion: The combination of Cisplatin, Paclitaxel and Doxorubicin demonstrates a marginal PFS improvement, but no additional survival benefit when compared with the standard Carboplatin/Paclitaxel regimen. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Advanced; Anthracycline; Carboplatin; Chemotherapy; Cisplatin; Doxorubicin; First line; Initial; Ovarian cancer; Paclitaxel